Essential statistics for economics, business and management - Bradley, Teresa (John Wiley & Sons, 2007)
Intended for introductory undergraduate courses and for the statistics component of courses in quantitative methods, this text will help students learn how to start a problem, complete the calculations, and report the results in a way that makes sense to a non-statistician